PERSEPSI UJARAN DALAM VIDEO PERMAINAN ABC LIMA DASAR MENGGUNAKAN MODEL COHORT - Titis Putri Pamungkas (Universitas Islam Malang, 2022)
Speech perception is the process of interpreting an utterance. Perception of speech includes hearing, interpretation, and understanding of the utterances conveyed by speakers. In this article, we will discuss the perception of speech in a psycholinguistic context through traditional games. The chosen traditional game is called ABC Five Basics, the writer chose this game because this game is unique. Can sharpen children's intelligence in remembering and mastering words. The purpose of writing this article is to describe the perception of speech through the ABC Five Basics game using the Cohort model.